Analysis strategy configurations in risk taking using fuzzy set qualitative comparative analysis model - Yang, Gang; Bai, Xueyan; Yang, Shiyu (Technological and Economic Development of Economy, 2023)
Risk-taking is a key factor in corporate competitive advantage, and economic development. The type of strategic configuration that can drive high-level risk-taking is a problem worthy of attention. This study takes 2,219 listed firms in China as samples and performs a fuzzy set qualitative comparative analysis (fsQCA) to explore the linkage effect and path choice of strategic change, corporate social responsibility, innovation, diversification, and financialization with corporate risk-taking (CRT). It finds that: (a) a single strategy does not constitute a necessary condition for high-level CRT; (b) three types of adaptive schemes exist for high-level CRT, among which the risk-taking level is the highest under the path of “Innovation, diversification, and financialization”; and (c) the driving paths of CRT in different regions, industries, and ownership show obvious differences.